Evaluación de susceptibilidad a deslizamientos y elementos expuestos en el área urbana de la parroquia Facundo Vela, 2020 - Yanchaliquin Punina, Maximo Jesus (2021)
In the present investigative work entitled "Evaluation of susceptibility to landslides and exposed elements in the urban area of the Facundo Vela parish", the study area is located in the Guaranda canton, Bolívar province, its objective is to identify factors, landslide zones and threat levels, determine the exposed elements (buildings, roads, sewers, piped water) and propose risk reduction strategies in the event of landslides. For the evaluation of the threat of landslides, the Mora Vahrson methodology was applied, which was adapted to the study area, in which the indicators are established such as: the triggering and conditioning factors to which we have assigned a numerical value according to the incidence , a weighting weight was established for each of the variables, when multiplying the indicator value by weighting weight, a maximum value is obtained, whose sum allows to determine the index and level of landslide threat, the maps of each variable were correlated and represented in the Arc Gis software (10.5). Regarding the result, one identified the conditioning factors; The most predominant in terms of lithology is volcanic sandstone, geomorphology with mountainous relief, land use with crops and a slope greater than 45 degrees of inclination; The triggers with an annual precipitation is 1500 to 2500 mm, being the highest annual precipitation that occurs in the area, in terms of seismicity according to the NEC-2015 the study area is within the seismic zone IV of high danger with an acceleration of 0.35 g acceleration in rock; By correlating the conditioning and triggering factors, the map with threat levels was obtained, which in the urban area of the Facundo Vela parish predominates the high and medium level. With respect to result two, from the hazard level map of the urban area, it was correlated with the exposed element maps; With respect to main buildings, most of the buildings, urban roads, and drinking water and sewerage networks present a high level of explosion to the threat of landslides. The aforementioned results allowed proposing strategies for reducing risks in the event of landslides, the proposal is considered viable: political, legal and institutional, since there is the interest of the authorities, institutions and the population to implement the necessary proposals as a strategy reduction. Keywords: landslide threat, conditioning and triggering factors, landslide reduction strategies.